Meningkatkan kualitas alat instrumen dalam pelatihan menyusun konstruksi soal-soal level Higher Order Thinking Skills (HOTS) - Alimuddin Alimuddin; Usman Mulbar; Ahmad Zaki (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The PKM program is carried out by the method of providing training and guidance to participants regarding the preparation of HOTS level questions to increase activities in carrying out learning with the aim of (1) to improve the quality of evaluation tools, (2) participants can implement properly compiling HOTS level questions in the learning process, and (3) participants can disseminate or disseminate knowledge about HOTS level questions. The main target audience for the PKM Program activities are school supervisors, school principals and school teachers in Tinggimoncong sub-district, Gowa district, South Sulawesi province. The results obtained in PKM program activities are increased knowledge and concept of HOTS level questions for PKM program participants, increased skill in preparing HOTS level questions for PKM program participants, PKM program participants can make examples and arrange HOTS level questions in learning class , and PKM program participants can implement the preparation of HOTS level questions in learning at school. Other results obtained were increased motivation of participants in knowing the materials for formulating HOTS level questions and the high enthusiasm of participants in disseminating or disseminating PKM program results, especially in the formulation of HOTS level questions. Outputs of PKM activities are (1) increasing participant's knowledge regarding activity materials, (2) scientific articles published at national seminars, and (3) publications on PKM implementation on online media.